Determinants Of Employee Turnover In Public Universities In Nyeri County - Saverio, Emily Karimi; Githui, Donatus Mathenge; Ngure, Susan (Advances in Social Sciences Research Journal, 2018)
Many organizations are facing the challenge of retaining productive employees to their competitors due to various reasons. Leadership style and career growth are becoming a major consideration for employees’ desire to stay or leave the organization. To minimize turnover, institutions of higher learning are concerned with identifying the major reasons behind it The study seeks to analyze the leadership styles and career growth in public universities as a determinant of employee turnover. The study adopted a descriptive research design. Organizations embracing appropriate leadership styles are less likely to have employee turnover. Most employees would prefer organizations that involve them in decision making and have proper channels to air their views and grievances. The results revealed that leadership styles had a significant effect on employee turnover in public universities while career development had insignificant effect on employee turnover in these universities. Data was analyzed using statistical package for social sciences (SPSS) software to generate descriptive and inferential statistics. Multiple regression analysis was used to determine the statistical relationship between the independent and dependent variables. The study recommended that universities should put in place mechanisms and policies of addressing human resource issues relating to leadership and growth of opportunities inorder to reduce turnover.